(untitled) (Lafia Journal of Scientific and Industrial Research, 2023)
Schistosomiasis, also known as bilharziasis or snail fever is primarily a tropical parasitic disease caused by eggs of adult stages of Schistosoma haematobium. Schistosomiasis has significant economic and public health consequences in many tropical and subtropical countries. This research aimed to determine the prevalence of urinary schistosomiasis among pupils of primary schools in Keffi LGA. A survey of S. haematobium was carried out among primary school pupils between the ages of 4 - 12 years in three primary schools that were selected randomly. A Questionnaire was administered to obtain demographic data. A total of 250 urine samples were examined, comprising 152 from males and 98 from females. The sedimentation technique was used, and urine deposits were examined microscopically. The overall prevalence of infection with Schistosoma haematobium in this study was 31.6%. Prevalence of disease varied among different schools, with the highest prevalence recorded at NSUK Demonstration School (20.8%) followed by LEA Primary School GRA (7.2%) while ECWA Primary School had the least prevalence of 3.6%. Males had 20.8% while females had 10.8% prevalence about Gender. Infection prevalence based on age was recorded as highest among the 10 – 12 age group with a prevalence of 20.4%. For prevalence based on source of water, those who used well water had a prevalence of 23.2%; while for prevalence based on parent’s occupation, Farmers had the highest with 22.4%. The study confirmed the prevalence of S. haematobium in the study area.